Job stressors encountered by the municipal government employees of Ilocos Norte and their level of job satisfaction - Rasalan, Mark Christian A. (Laoag City : [s.n.], 2018)
This study determined the job stressors encountered by the municipal government employees of Ilocos Norte along the three levels of stressors : individual, group, and organization, and their level of job satisfaction along the following factors: salaries and benefits, work itself, relationship with peers, relationship with superiors, working conditions , and social factors. It also determined the significant difference between their level of job satisfaction when grouped according to class of municipality, and the significant relationship between the job stressors and the employees' job satisfaction.
Bibliography: pages 82-85.
CHED-La Union
Keywords: Job satisfaction